Oscillating primary transcripts harbor miRNAs with circadian functions - Wang, Haifang (Sci Rep, 2016)
The roles of miRNAs as important post-transcriptional regulators in the circadian clock have been suggested in several studies. But the search for circadian miRNAs has led to disparate results. Here we demonstrated that at least 57 miRNA primary transcripts are rhythmically transcribed in mouse liver. Most of these transcripts are under the regulation of circadian transcription factors such as BMAL1/CLOCK and REV-ERBα/β. However, the mature miRNAs derived from these transcripts are either not oscillating or oscillating at low amplitudes, which could explain the inconsistency of different circadian miRNA studies. In order to show that these circadian primary transcripts can give rise to miRNAs with circadian functions, we over-expressed one of them, miR-378, in mouse by adenovirus injection. We found a significant over-representation of circadian oscillating genes under-expressed by miR-378 over-expression in liver. In particular, we observed that miR-378 modulates the oscillation amplitudes of Cdkn1a in the control of cell cycle and Por in the regulation of oxidation reduction by forming partnership with different circadian transcription factors. Our study suggests that circadian transcription of miRNA at primary transcript level can be a good indicator for circadian miRNA functions.